2023
DOI: 10.1101/2023.01.11.523570
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protein aggregation in plant mitochondria inhibits translation and induces an NAC017-dependent ethylene-associated unfolded protein response

Abstract: Loss of Lon1 in plant mitochondria led to stunted plant growth and accumulation of nuclear-encoded mitochondrial proteins, including Lon1 substrates, while mitochondrial-encoded proteins typically decreased in abundance. Lon1 mutants contained protein aggregates in the mitochondria matrix which were enriched in PPR-containing proteins and ribosomal subunits of the translation apparatus and were slowed in mitochondrial RNA splicing, editing and general translation rate. Transcriptome analysis showed multiple or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 44 publications
4
3
0
Order By: Relevance
“…The atg5 mutant was utilized to investigate whether im-paired autophagy elicits mitochondrial unfolded protein responses, illuminating the potential contribution of diminished autophagic flux in lon1 mutants to unfolded protein responses. We found that the majority of mitochondrial proteases reported that UPR mt [26,27], UPR cp [28], and UPR er [29] target genes are significantly upregulated in lon1-2 and lon1-2atg5-1 (Figure 3B-E, Supplementary Data S2), particularly pronounced in lon1-2 which was reported recently [20]. However, this phenomenon was not observed in atg5-1, demonstrating that the absence of ATG5 does not significantly induce UPR mt , and the downregulation of autophagy levels in the lon1 mutant is not the main cause of inducing UPRs or mitochondrial protease upregulation.…”
Section: Unfolded Protein Responses Are Not Associated With Autophagy...supporting
confidence: 82%
See 4 more Smart Citations
“…The atg5 mutant was utilized to investigate whether im-paired autophagy elicits mitochondrial unfolded protein responses, illuminating the potential contribution of diminished autophagic flux in lon1 mutants to unfolded protein responses. We found that the majority of mitochondrial proteases reported that UPR mt [26,27], UPR cp [28], and UPR er [29] target genes are significantly upregulated in lon1-2 and lon1-2atg5-1 (Figure 3B-E, Supplementary Data S2), particularly pronounced in lon1-2 which was reported recently [20]. However, this phenomenon was not observed in atg5-1, demonstrating that the absence of ATG5 does not significantly induce UPR mt , and the downregulation of autophagy levels in the lon1 mutant is not the main cause of inducing UPRs or mitochondrial protease upregulation.…”
Section: Unfolded Protein Responses Are Not Associated With Autophagy...supporting
confidence: 82%
“…The downregulation of autophagy flux in lon1 mutants, as discovered in this study, along with the reported upregulation of unfolded protein responses [20], can lead to changes not only in the abundance of specific proteins but also in the relative proportion of cellular compartments in plants. To investigate the possibility of changes in the relative proportion of cellular compartments, we conducted label-free quantitative mass spectrometry using root total proteins (Supplementary Data S1).…”
Section: Lon1 Loss Of Function Changes In Relative Proportion Of Cell...supporting
confidence: 59%
See 3 more Smart Citations